A persistent giant Eustachian valve: functional tricuspid atresia in a newborn. (18th January 2018) - Sideris, Konstantinos; Vodiskar, Janez; Lange, Ruediger; Cleuziou, Julie
Abstract: Persistent right valve of the systemic venous sinus is a rare anomaly with anatomical variations. This anomaly may present as an obstructive structure that can inhibit the antegrade flow through the tricuspid valve. We report on a 4-day-old neonate who presented with pronounced peripheral and central cyanosis. Echocardiographic examination showed a giant Eustachian valve moving towards the tricuspid valve during late systole and leading to complete obstruction of the inflow. Blood flow was redirected through the persistent foramen ovale, producing a right-to-left shunt.